Optimizing Competitive Advantage of Islamic Madrasahs Through the 7P Marketing Mix: A Comparative Study with ASEAN Perspectives - Yosef Budiman; Yadi Suryadi; Asep Suryana; Johar Permana; Eka Prihatin (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Competition among senior high schools in Indonesia is intensifying, thus encouraging Madrasah Aliyah Negeri (MAN), as a state Islamic senior high school, to adopt more systematic, transparent, and accountable strategies to maintain institutional credibility and stakeholder engagement in an increasingly competitive educational environment. This study aims to analyze the strategic role of the 7P marketing mix: Product, Price, Place, Promotion, People, Process, and Physical Evidence in shaping competitive advantage in state Islamic senior high schools. This study used a quantitative, explanatory design and was conducted at one of the madrasas in Bogor Regency, West Java. Data were collected through a structured, validated questionnaire administered to 203 11th-grade students, who were the primary users of academic and non-academic services. Data analysis was performed using descriptive statistics, Pearson correlation, and multiple linear regression to test the partial and simultaneous relationships between marketing mix dimensions and competitive advantage. The results show that the 7P marketing mix model simultaneously explains a significant proportion of the variance in competitive advantage (R² = 0.634). Although all 7P dimensions have a positive and significant relationship, Process, Physical Evidence, and Product emerged as the most dominant predictors. This finding confirms that competitive advantage in public Islamic senior high schools is determined not only by academic achievement, but also by the quality of governance, educational service systems, physical learning environments, curriculum coherence, and an organizational culture aligned with Islamic values. This study confirms the relevance of the 7P marketing mix as an effective managerial framework and recommends strengthening process-based governance, developing infrastructure, and integrating the curriculum to support institutional sustainability.